Tafsir Method of Tartib Nuzuli: An Analytical Study of Muhammad Darwazah's Kitab al-Tafsir al-Hadith and Muhammad al-Jabiri's Kitab Fahm al-Qur`an al-Hakim - Badruzaman, Abad; Aziz, Thoriqul (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2023)
The study of tafsir tartib nuzuli is still quite rare. This study seeks to complete the study. Tafsir tartib nuzuli is still considered “strange” by the majority of Muslims. This study is library research using a descriptive-analysis method. There are at least four mufasirs (interpreters) who use the tafsir method of tartib nuzuli, namely Bayan al-Ma'ani by Abdul Qadir Huwaisy (Iraq: 1880-1978), Al-Tafsir al-Hadith by Muhammad Darwazah (Syria: 1887-1984), Ma'arij al-Tafakkur by Abdurrahman al-Maidani (Syria: 1927-2004), and Fahm al-Qur`an al-Hakim by Muhammad al-Jabiri (Morocco: 1935-2010). Of the four books of nuzuli interpretation, this paper will focus on two books, namely Al-Tafsir al-Hadith and Fahm al-Qur`an al-Hakim. The tafsir method of nuzuli has its own characteristics and contributions compared to other methods of interpretation. Tafsir tartib nuzuli can be an alternative method in portraying the Prophet’s da’wah journey / Islamic transformation from the time of Muhammad's prophethood until his death. Tartib nuzuli interpretation is more related to the chronology of the Prophetic Sirah Nabawiyah (Prophetic Journey) as narrated in the books of Sirah. Studi tentang tafsir tartib nuzuli masih cukup jarang dilakukan. Kajian ini berusaha untuk melengkapi studi tersebut. Tafsir tartib nuzuli dianggap masih ”asing” oleh mayoritas umat Islam. Kajian ini bersifat kepustakaan (library research) dengan menggunakan metode deskriptif-analisis. Setidaknya ada empat mufasir yang menggunakan metode tafsir tartib nuzuli yaitu Bayan al-Ma’ani karya Abdul Qadir Huwaisy (Irak: 1880-1978), Al-Tafsir al-Hadits karya Muhammad Darwazah (Suriah: 1887-1984), Ma’arij al-Tafakkur karya Abdurrahman al-Maidani (Suriah: 1927-2004), dan Fahm al-Qur`an al-Hakim karya Muhammad al-Jabiri (Maroko: 1935-2010). Dari empat kitab tafsir nuzuli tersebut, tulisan ini akan fokus pada dua kitab, yaitu Al-Tafsir al-Hadits dan Fahm al-Qur`an al-Hakim. Metode tafsir nuzuli memiliki ciri khas dan kontribusi tersendiri dibanding metode tafsir lain. Tafsir tartib nuzuli dapat menjadi metode alternatif dalam memotret perjalanan dakwah Nabi/formasi Islam sejak masa kenabian Muhammad sampai wafatnya. Tafsir tartib nuzuli lebih sinkron dengan kronologi Sirah Nabawiyah sebagaimana dinarasikan dalam kitab-kitab sirah.